The stem fixation technique do influence the tibial alignment in TKA revisions. A comparative study between cemented and cementless / hybrid cemented tibial stems using 3D-CT. Issue 4 (27th April 2017) - Schiapparelli, Filippo-Franco; Amsler, Felix; Hirschmann, Michael
Aims and Objectives: : Purpose of the study was to investigate if the fixation technique for intramedullary stems in total knee arthroplasty revisions (rTKA), influence the alignment of the components, leg axis and the rates of complications, reoperations and revisions. Materials and Methods: : Sixteen patients with cemented tibial stems (Group C) and twenty-six patients with either cementless or hybrid cemented tibial stems (Group PF) were collected. All patients underwent regular clinical follow-up (41.5 months) and postoperative 3D-CT scans. Mean values of the three-dimensional rTKA component position and of the leg axis were compared between groups with the T-test. The tibial components were graded on the transversal plane into internal, neutral and external rotated, and, on the coronal plane, in neutral and varus/valgus aligned. The graded measurements and the incidences of postoperative complications, reoperations and revisions were analysed with a Chi 2 -Test. Results: : The mean measurements of the component position did not significantly differ between groups (p < 0.05). Group C showed a tendency to internal rotation (Group C: 62.5%; Group PF: 34.6%) and a significant higher coronal alignment accuracy (p = 0.004). Group PF instead a tendency to external rotation (Group C: 25.0%; Group PF: 46.2%) (p = 0.094). Both groups presented a neutral leg alignment (Group C: 0.00° ± 3.37; Group PF: 1.04° ± 2.6) (p = 0.268). Group PF showed a tendency to more complications (Group C: 35.7%; Group PF: 60.9%; p = 0.138). No significant differences were seen between rates of reoperations (Group C: 35.7%; Group PF: 30.4%; p = 0.565) and revisions (Group C: 28.6%; Group PF: 8.7%; p = 0.894). Conclusion: : The stem fixation technique influence the tibial component alignment. A more accurate coronal alignment was achieved in Group PF.